PERUBAHAN PERILAKU KOMUNIKASI KARYAWAN SUB. BAG HUMAS DAN PENAGIHAN PDAM KOTA SALATIGA SEBELUM BULAN RAMADHAN HINGGA BULAN RAMADHAN TAHUN 2014 - Clarissa Marscalofa; Richard G Mayopu; George Nicholas Huwae (Universitas Kristen Satya Wacana, 2015)
Behavior is someone response orreaction towards the external stimulus (stimuli from the outside). In a company or agency, individual behavior is strongly influenced by the work environment, thus forming a pattern of organizational behavior. Religious rituals are still practiced todays, unconsciously limit people behavior. Indications of changes in employee behavior also occur on Sub.Bag.Humas dan Penagihan PDAM Salatiga. This research was conducted to determine how behavior and communication changes caused by particular moment (Ramadhan). The method used in this research is qualitative ethnographic that intens to understand social phenomenon of the changing pattern of behavior and communication that occurs at specific moment (Ramadhan). The results of this research, stated that the behavior and communication undergo changes because of special moment which it has implications on employee’s performance and even the rules in the company.Keywords: Behavior modifications, Communication, Public Relations (Humas)